A new and rapid UV-Visible spectrophotometric method for benidipine hydrochloride determination: Development and validation - AL-japairai, Khater Ahmed Saeed; Syed, Mahmood; Nadiya, Abdul Halim; Almurisi, Samah Hamed (Springer, 2023)
A simple, sensitive and specific ultraviolet spectrophotometric method has been established for the determination of benidipine hydrochloride. The wavelength of maximum absorbance (λmax) for benidipine was found to be 237 nm. Linearity of this method was observed in a range of 2.0 – 16.0 μg/mL. The method showed high sensitivity with good reproducibility of results. The limit of detection and the limit of quantification were 0.34 and 1.02 μg/mL, respectively. The calibration curve was constructed by plotting a graph of the absorbance versus concentration. The coefficient of correlation was higher than 0.99. The regression equation of this curve is y = 0.0544x – 0.0526. The percentage of drug recovery was found in the acceptable range (99.72 – 101.66%), and the coefficient of variation for the precision of this method was found to be less than 2.0. The proposed method can be suitable for the analysis of benidipine in tablet formulations for quality control purposes.